Contribution of Discipline to Forming Employee Perfomance at the Community Health Center (Puskesmas) of Raya Pematangsiantar City - Vivi Candra; Sherly Sherly; Edy Dharma (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2020)
This study aims to determine the effect of discipline on the performance of employees of the Community Health Center (Puskesmas) of Raya Pematangsiantar City. This research used the design of literature and field research. The research method used was the causality method with a quantitative approach. The type of data used in this study was qualitative and quantitative data. Data sources consisted of primary and secondary data. The population and sample used in this study were 34 permanent employees. Data collection was done by questionnaire, interview, and documentation. The analysis technique used was qualitative descriptive and quantitative descriptive analysis consisting of multiple linear regression, correlation test, the test of determination and hypothesis. The results of this study concluded that employee discipline and performance was good. Regarding the results of the hypothesis, it shows that discipline has a positive and significant effect on employee performance.